Addressing the Academic Needs of Adolescents With Autism Spectrum Disorder in Secondary Education. (March 2014) - Fleury, Veronica P.; Hedges, Susan; Hume, Kara; Browder, Diane M.; Thompson, Julie L.; Fallin, Kathy; El Zein, Farah; Reutebuch, Colleen Klein; Vaughn, Sharon
The number of individuals with Autism Spectrum Disorder (ASD) who enter secondary school settings and access the general education curriculum continues to grow. Many educators may find they are not prepared to adapt their instruction to meet both state standards and the diverse needs of the full spectrum individuals with ASD, which has implications for postsecondary success. In this article, we present an overview of current knowledge around academic instruction for this population, specifically (a) how characteristics associated with ASD can impact academic performance, (b) academic profiles of individuals with ASD across content areas, and (c) interventions that have been successful in improving academic outcomes for this population, including special considerations for those individuals who take alternate assessments based on alternate achievement standards. We conclude by offering suggestions for future research and considerations for professional development.